Neural correlates of attitudes and risk perception for food technology topics. (March 2020) - Davis, Tyler; LaCour, Mark; Beyer, Erin; Finck, Jessica L.; Miller, Markus F.
Highlights: People view foods made with technologies as riskier and less positive. Lateral prefrontal cortex tracks perceptions of risk for food technology topics. Medial prefrontal cortex tracks positive attitudes for food technology topics. Brain activation predicts risk perception and attitude change for hormones and GMOs. Abstract: Food technologies provide numerous benefits to society and are extensively vetted for safety. However, many technological innovations still face high levels of skepticism from consumers. To promote development and use of food technologies, it is critical to understand the psychological and neurobiological processes associated with consumer acceptability concerns. The current study uses a neuroscience-based approach to understand consumer attitudes and perceptions of risk associated with food technologies and investigate how such attitudes impact consumer's processing of information related to food technologies. We used functional magnetic resonance imaging (fMRI) to measure brain activation while participants processed infographics related to food technology topics. For technology topics perceived as riskier (antibiotics and hormones), activation was higher in areas of the lateral prefrontal cortex that are associated with decisional uncertainty. In contrast, technology topics that were viewed more favorably (sustainability and animal welfare) tended to activate the ventromedial prefrontal cortex, a region that processes positive affect and subjective value. Moreover, for information about hormones, the lateral PFC activation was associated with individual differences in resistance to change in risk perception. These results reveal how attitudes and risk perception relate to how the brain processes information about food technologies and how people respond to information about such technologies.